SAT0464 Disease Status Influences the Balance and Cytokine Profile in Patients with Juvenile Idiopathic Arthritis. (23rd January 2014) - Almanzar, G.; Sustal, K.; Trippen, R.; Höfner, K.; Prelog, M.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is an inflammatory disorder with heterogeneous clinical presentation. IL-17-producing T-cells (Th17) have been identified as pro-inflammatory cells in several autoimmune conditions. Objectives: This study evaluated the phenotype and the cytokine-production profile of T-cells in JIA patients with active disease (group 1, n=17), remission on medication (group 2, n=39), remission off medication (group 3, n=10), disease flare after remission (group 4, n=16) and healthy donors (HD, n=28). Methods: The phenotype characterization and the intracellular production of IFNgamma, TNFalpha, and IL-17 on naive (CD28+CD45RO-), memory (CD28+CD45RO+), effector (CD28-CD45RO+), terminally differentiated T-cells (CD28-CD45RO-) and regulatory T-cells (Tregs, CD25+CD127-FoxP3+) CD4+ T-cells were investigated by flowcytometry. Results: IFNgamma-producing CD4+ T-cells (4.9% versus 6.9%) and Tregs (2.9% versus 3.8%) were significantly lower in JIA than HD. Moreover, memory CD4+ T-cells produced lower amounts of IFNgamma in JIA group 4 (6.3%), group 1 (6.3%) and group 2 (7.6%) compared to HD (11.3%). Interestingly, the memory CD4+ T-cell population also showed lower TNFalpha production in the same groups (group 4:20.3%; group 1:18.5%; group 2:20.0%; HD:29.9%). No differences were observed in the IL-17 production by CD4+ T-cells between JIA and HD. However, patients with disease flare showed higher proportions of IL-17-producing CD4+CD45RO-CD28-CD27- T-cells (1.3%) than patients in remission off medication (0.6%) Conclusions: Our findingssuggest, depending on disease activity, an imbalance in the cytokine production profile in memory and effector T-cell subpopulations in JIA patients. This may be increasingly relevant for novel therapeutic approaches with early treatment of active disease with biologic drugs. Disclosure of Interest: None Declared